2016
DOI: 10.1177/2156587215605903
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-inflammatory and Some Possible Mechanisms of Antinociceptive Effect of Ferula assa foetida Oleo Gum Resin

Abstract: Asafetida is well known for its medicinal and therapeutic values in Iranian folk medicine. This study was conducted to investigate the antinociceptive and anti-inflammatory effects of asafetida. In hot plate test, asafetida exhibited a significant antinociceptive effect at all administered doses and the most effective dose was 10 mg/kg. The highest maximum potent effect was observed 15 minutes after asafetida administration. The antinociceptive effect of asafetida was not reversed by administration of any anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…The samples were run in triplicate and the mean value of three of them was recorded. The percentage inhibition was plotted against the sample concentration in order to calculate the IC 50 values, which is the concentration (μg/ml) of asafoetida that causes 50% loss of DPPH activity [12] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were run in triplicate and the mean value of three of them was recorded. The percentage inhibition was plotted against the sample concentration in order to calculate the IC 50 values, which is the concentration (μg/ml) of asafoetida that causes 50% loss of DPPH activity [12] .…”
Section: Methodsmentioning
confidence: 99%
“…In Iranian folk medicine, asafoetida is considered as an antispasmodic, anthelminthic, sedative, anticonvulsant and carminative agent [11] . Recent pharmacological and biological studies have verified several pharmacological activities such as antioxidant [12] , antileishmanial [13] , anticonvulsant [14] anti-diabetic [15] , antispasmodic [16] , hypotensive [17] , and antinociceptive [18] from this oleo gum resin. A meta-analysis study showed that in countries like Japan, Russia, China, Indonesia, the rate of cancer is higher in the comparison of countries that usage of asafoetida is common [19] .…”
Section: Introductionmentioning
confidence: 99%
“…The hot-plate test was carried out according to the method previously described. [11] Briefly, before the initial of experiment, mice were habituated to a Plexiglas cylinder for 5 min. In these experiments, the hot-plate apparatus was maintained at 54±0.1°C.…”
Section: Hot-plate Testmentioning
confidence: 99%
“…In folk medicine, the roots of this plant are used as perceived anthelmintic, anticarcinogenesis, anti-HIV, antimicrobial, antirheumatic, antispasmodic, diuretic, and emmenagogue [14]. The pharmacological and biological studies of Ferula assa-foetida have also reported a large number of drug activities such as antioxidant [22], antileishmanial [23], anticonvulsant [24], anti-diabetic [25], antispasmodic [26], hypotensive [27], and antinociceptive [28]. Recent statistics have shown that cancer rates are higher in countries such as Japan, Russia, China, and Indonesia in comparison to countries using Ferula assa-foetidathis is common [29].…”
Section: Introductionmentioning
confidence: 99%